2007
DOI: 10.1001/archinte.167.21.2304
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index, Glycemic Load, and Cereal Fiber Intake and Risk of Type 2 Diabetes in US Black Women

Abstract: Background: Previous studies of carbohydrate quality and risk of type 2 diabetes mellitus have yielded inconsistent findings. Because diet is in part culturally determined, a study of dietary factors in US black women is of interest. Methods: We used data from the Black Women's Health Study, a prospective cohort study of 59 000 US black women, to examine the association of glycemic load, glycemic index, and cereal fiber with risk of type 2 diabetes. Diet was assessed at baseline in 1995 with a modified version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 23 publications
10
132
2
Order By: Relevance
“…Previous work has identified many dietetic problems in older adults with T2DM (28,29) and our finding on nutritional status (85.7% at risk of being malnourished) support this previous work. In this specific population, malnutrtional status is related to the glycemic control, such the glycemic index of nutrients (28,29) or reduced Zinc and Vitamin C levels (30). The poor nutritional status exhibited by those with T2DM is a barrier to gaining muscle tissue and strength, which may be also related to poor insulin tissue sensitivity (10).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work has identified many dietetic problems in older adults with T2DM (28,29) and our finding on nutritional status (85.7% at risk of being malnourished) support this previous work. In this specific population, malnutrtional status is related to the glycemic control, such the glycemic index of nutrients (28,29) or reduced Zinc and Vitamin C levels (30). The poor nutritional status exhibited by those with T2DM is a barrier to gaining muscle tissue and strength, which may be also related to poor insulin tissue sensitivity (10).…”
Section: Discussionsupporting
confidence: 90%
“…Similar impairments may be a possible explanation for the lower functional capacity reported by our participants, which has been also reported to play an important role in HRQoL among T2DM patients (9). Previous work has identified many dietetic problems in older adults with T2DM (28,29) and our finding on nutritional status (85.7% at risk of being malnourished) support this previous work. In this specific population, malnutrtional status is related to the glycemic control, such the glycemic index of nutrients (28,29) or reduced Zinc and Vitamin C levels (30).…”
Section: Discussionsupporting
confidence: 89%
“…The Shanghai Women's Health Study concluded that women whose diets had the highest glycemic index were 21 percent more likely to develop type 2 diabetes than women whose diets had the lowest glycemic index [14]. Similar findings were reported in the Black Women's Health Study [15]. A diet program that manages the glycemic load aims to avoid sustained blood-sugar spikes and can help avoid onset of type 2 diabetes.…”
Section: Introductionsupporting
confidence: 52%
“…However, the two studies Table 3 Regression coefficients predicting log high-sensitivity C-reactive protein from linear mixed models Table 4 Regression coefficients predicting log high-sensitivity C-reactive protein from multivariable linear mixed models controlled for age, BMI, and smoking in the analysis, although residual confounding by these factors is still possible. In a recent publication examining the association of GI, GL, and cereal fiber intake with risk of type 2 diabetes in a cohort of United States black women, risk of diabetes was not statistically significantly associated with GL [26]. The investigators explained that it can be difficult to study GL because of its high correlation with total carbohydrate intake, because cereal fiber intake increased with quintiles of GL, whereas whole grains (a major source of cereal fiber) contributed to GL.…”
Section: Discussionmentioning
confidence: 99%